Reproductive challenges in Indian dairy farming: an analysis of repeat breeding and infertility in Tamil Nadu - Thanammal Ravichandran; Garima Digdarshika; Mizeck G. G. Chagunda; Arunkumar Krishnamoorthy; P. Shanthra; Kiruthika Nallasamy; Chitra Ramasamy; Mohanamani Palanisamy (Tropical Animal Health and Production, 2026)

Multi-trait index based Elucidation of drought tolerance potential of Saccharum spontaneum - T. Lakshmi Pathy; V. Vinu; R. Arunkumar; Gopalareddy Krishnappa; H. K. Mahadeva Swamy; R. Valarmathi; K. Dhanapal; Amaresh; P. Govindaraj; G. Hemaprabha; Bakshi Ram (Plant Physiology Reports, 2025)

Biological and genomic characterization of a cypovirus isolated from golden muga silkworm, Antheraea assamensis Helfer (Lepidoptera: Saturniidae) - Iyyangar Deepika; Abhishek Singh; Indira Kumar; Gowtham K; Roja Gnanasekaran; Himanshu Dubey; Rajal Debnath; Pawan Shukla; Kangayam M. Ponnuvel; Vikram Kumar; K.P. Arunkumar; Hanamant Gadad; et al. (Journal of Invertebrate Pathology, 2025)

Stilt floor optimization based on stiffness and column contribution - R. Kavitha; G. Keertiga; D. Suryakrishnan; N. Santhakrishnan; M. Arunkumar (Innovative Infrastructure Solutions, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Phenological Stages of Pink Pulp Dragon Fruit (Hylocereus costaricensis Web.): Codification and Description According to the Extended BBCH Scale Under Field Conditions - M. Kavino; G. Arunkumar (Applied Fruit Science, 2024)

Automatic Detection and Analysis of the Shoreline Change Rate at Maravanthe Coast, India - Arunkumar Yadav; Geetha Kuntoji; Chandrashekarayya G. Hiremath; Nagendra H. Narasimha; Sheetal Mutagi (Marine Geodesy, 2024)

Combating Alcohol Adduct Impurity in Immunosuppressant Drug Product Manufacturing: A Scientific Investigation for Enhanced Process Control - Vasanthakumar Sekar; Devarajan Vedhachalam; ArunKumar VB; Sivananthan Sivaraman; Venkatakrishnan Janakarajan; Sai Sethuraman; Sandeep G. Shiroor; Jean-Marie M. Geoffroy (Pharmaceutical Research, 2024)

Efficiency of female age of egg parasitoids on parasitism of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) eggs of various ages - K. Veena; Arunkumar Hosamani; A. Prabhuraj; Shivanand G. Hanchinal; Mallikarjun Kenganal; Sharanabasappa S. Deshmukh (Journal of Plant Diseases and Protection, 2024)

(Re)-thinking the red seaweed biomass for biofuel production to meet sustainable development goals toward circular bioeconomy - M. P. Sudhakar; K. Arunkumar; G. Dharani; Thangavel Mathimani (Energy, Ecology and Environment, 2024)

Effects of MWCNT nanoparticles injection points on incompressible laminar hydrogen flow through discrete phase modeling by CFD approach - Sandhanasamy Devanesan; Mohamad S. Alsalhi; Nassar Asemi; G. Arunkumar (Fuel, 2023)

Persistence of antibody response in chikungunya - Shweta Chelluboina; S. Robin; S. Aswathyraj; G. Arunkumar (VirusDisease, 2019)

A report of human papilloma virus-16 associated vaginal carcinoma after thirty-two years of successful radiation therapy for cervical cancer - Gazal Jain; Sasidharanpillai Sabeena; Akhila Vasudeva; Anjali Mundkur; Srilatha Parampalli Srinivas; G. Arunkumar; Pratap Kumar (VirusDisease, 2018)

Hand, foot and mouth disease (HFMD): emerging epidemiology and the need for a vaccine strategy - S. Aswathyraj; G. Arunkumar; E. K. Alidjinou; D. Hober (Medical Microbiology and Immunology, 2016)

Genotyping of human adenoviruses circulating in Southwest India - C. Akhil; P. G. Suresha; S. Sabeena; M. Hindol; G. Arunkumar (VirusDisease, 2016)

Pilot scale thin film plate reactors for the photocatalytic treatment of sugar refinery wastewater - S. Saran; G. Kamalraj; P. Arunkumar; S. P. Devipriya (Environmental Science and Pollution Research, 2016)

Recombination networks as genetic markers in a human variation study of the Old World - Asif Javed; Marta Melé; Marc Pybus; Pierre Zalloua; Marc Haber; David Comas; Mihai G. Netea; Oleg Balanovsky; Elena Balanovska; Li Jin; Yajun Yang; GaneshPrasad ArunKumar; et al. (Human Genetics, 2012)

Quercetin downregulates matrix metalloproteinases 2 and 9 proteins expression in prostate cancer cells (PC-3) - M. R. Vijayababu; A. Arunkumar; P. Kanagaraj; P. Venkataraman; G. Krishnamoorthy; J. Arunakaran (Molecular and Cellular Biochemistry, 2006)